"Say Ahhh": Experience and Views on Halitosis Management in the General Public in Victoria, Australia - Phyllis Lau; Stephanie Ibrahim; Amreen Hussain; Sarah Hu; Sung Jin; Michael Huang; Michael Khng; Ivan Darby (Elsevier, 2021)
Introduction: Halitosis is common and can have a significant impact on quality of life. It is attributed to both intraoral and extraoral causes. Although halitosis treatment depends on the aetiology, little is known about consumers' perception of halitosis causes and the types of assistance sought. The Say Ahhh Study aimed to explore the interprofessional care for halitosis and improve understanding by the general public. Phase 1 explored the perceptions of health care providers. This article reports the findings of Phase 2, which explored the general public's knowledge of halitosis, its management, and help-seeking behaviour. Methods: Patients and clients at 2 medical clinics, 3 dental clinics, and 2 pharmacies in Melbourne and rural Victoria were approached and invited to participate in a short semistructured interview. Qualitative data was thematically analysed. Results: A total of 122 participants (54 males, 66 females, 2 missing) were interviewed. Participants' past experience with halitosis influences their understanding of the cause. Halitosis was attributed mostly to poor oral hygiene and diet and less commonly to systemic disease. Their perception of the condition's severity influenced whether they seek professional help. Their perceived roles of health professionals and ease of access influenced their choice of health professionals to seek help from. Conclusion: The Victorian general public is aware of the causes of halitosis and the available treatment options. Choice of treatment and help-seeking behaviour are influenced by experience, perceived severity of the condition, and perceived role of health professionals and their accessibility.